2018
DOI: 10.1080/07481187.2017.1386734
|View full text |Cite
|
Sign up to set email alerts
|

What influences intentions to request physician-assisted euthanasia or continuous deep sedation?

Abstract: The increasing prevalence of euthanasia in Belgium has been linked to changing attitudes. Using National health survey data (N = 9651), we investigated Belgian adults' intention to ask a physician for euthanasia or continuous deep sedation in the hypothetical scenario of a terminal illness and examined its connection to sociodemographic and health characteristics. Respectively, 38.3 and 25.8% could envisage asking for euthanasia and continuous deep sedation. Those with very bad to fair subjective health and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our study makes several contributions to the literature. While previous studies have explored attitudes towards euthanasia and AS in the general population [30,[36][37][38][39][40][41], there are -to the best of our knowledge-no previous studies that have investigated both attitudes and behaviours (actual and planned membership in a right-to-die organisation) in the same population in parallel. This strategy allows to assess the associations of EOL preferences and trust in social or public institutions not just with AS-related attitudes but also corresponding behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Our study makes several contributions to the literature. While previous studies have explored attitudes towards euthanasia and AS in the general population [30,[36][37][38][39][40][41], there are -to the best of our knowledge-no previous studies that have investigated both attitudes and behaviours (actual and planned membership in a right-to-die organisation) in the same population in parallel. This strategy allows to assess the associations of EOL preferences and trust in social or public institutions not just with AS-related attitudes but also corresponding behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…A study on attitudes towards EOL decisions in the Dutch general public also reported no association between poor self-rated health and euthanasia acceptance [38], whereas some other studies have found a positive association of poor self-rated health with assisted suicide acceptance [41] and potential use of euthanasia [48].…”
Section: Experience As a Healthcare Proxy Increases Positive Assisted Suicide Attitudes And Behaviourmentioning
confidence: 94%
“…These generations may, therefore, be less concerned about controlling their EOL decisions than individuals from the post-World War II generation, who were exposed to more progressive ideas in the context of an increasingly secular society [47]. Although the literature seems to provide only mixed evidence on patterns in the association of age with acceptance of any active ending of life, lower levels of support for such practices among older age groups have been observed in other cross-sectional studies, and are typically interpreted as due to cohort effects along the lines of those described above [34,35,39,47,48]. These explanations seem to be further supported…”
Section: Education Is Associated With Individuals' Attitudes Towards Assisted Suicidementioning
confidence: 99%
“…Evidence from the Netherlands indicates that physicians may actively encourage patients to opt for palliative sedation rather than assisted dying for reasons of bureaucracy, as the latter entails substantial paperwork ( Bruinsma et al, 2013 ; Robjin et al, 2017 ). Both Anquinet et al (2012) and Scherrens et al (2018) report that informed of the two choices as alternatives, patients will have a preference for one or the other. Furthermore, palliative sedation is sometimes ritually organised similarly to assisted dying, including a family farewell ( Bruinsma et al, 2014 ).…”
Section: Ethical Issues Regarding Palliative Sedation and Assisted Dyingmentioning
confidence: 99%
“…Palliative sedation is controversial and is generally considered an extreme measure to be undertaken only in prescribed circumstances ( Materstvedt and Bosshard, 2009 ; Rietjens et al, 2018 ). Yet research evidence suggests that it occurs frequently ( Abarshi et al, 2017 ; Scherrens et al, 2018 ). In Belgium, for example, which features in this study, a 2013 nationwide survey found that it was used in 12% of all deaths ( Robijn et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%